Pelatihan Penggunaan Model Cooperative Integrated Reading and Composition (CIRC) Bagi Guru SMAN 4 Balikpapan untuk Meningkatkan Keterampilan Menulis Teks Ceramah Peserta Didik - Edi Sudarto; Luwes Handayani; Mufidah Mufidah; Swasti Maharani; Indah Ika Ratnawati (Jurnal SOLMA, 2023)
Background: Writing lectures is a creative-productive activity in which students must have experience and reliable references because lecture texts are informative, educative, and persuasive. Students are carried out through a literacy process. The purpose of this activity is to provide in-depth material to teachers about the CIRC learning model in order to improve students' lecture writing skills at SMAN 4 Balikpapan. Method: The activity was carried out at SMA Negeri 4 Balikpapan, the training was attended by Indonesian language teachers. After the training ended, the model was implemented in one of the classes. Selection is done by simple random sampling. Learning activities with the model are carried out in several meetings with the method used, namely cycles I and II consisting of planning, implementing, observing, and reflecting. Data collection techniques by means of tests, distributing questionnaires, and documentation. Results: Bahasa Indonesia teachers all understand the steps of the CIRC learning model and are willing to apply them to learning in class. As for the results of the implementation of the model, the pre-cycle consists of seven assessment indicators. From the results of the recap, the lowest is the assessment of attitudes in learning, namely 81%. Results of cycle I Of the 35 students, only 16 reached the KKM and 19 were still below the KKM. And cycle II of the 35 students 33 achieved the KKM score and only 2 had not reached the KKM score. The CIRC model can improve students' lecture writing skills at SMAN 4 Balikpapan.